Inter-Racial Effect on Electrocardiographic Abnormalities among Stroke Patients in Sub-Saharan Africa - Osarenkhoe, Osaretin John; Osarume, Aiwuyo Henry; G, Kweki Anthony; Alugba , Gabriel; Torere, Beatrice; Oluwasegun, Akinti M; Ovwasa , Henry; Ilerhunmwuwa , Nosakhare; Aghwana, Roy; Obazee , Emmanuel; et al. (International Journal of Health Sciences, 2023)
Purpose: The study aimed to determine the prevalence of electrocardiographic abnormalities in black stroke patients and to find out if the black race predisposes to increased electrocardiographic abnormalities as well as specific electrocardiographic abnormalities among the study population. Methodology: This was a cross-sectional analytical study carried out at the University of Benin Teaching Hospital Benin. The electrocardiographic abnormalities of one hundred and twenty (120) admitted black stroke patients in this study were compared with Goldstein study on Caucasians in the United States of America. The data were analyzed using the IBM SPSS statistics version 22. A p < 0.05 was considered significant. Results: The study demonstrated the prevalence of electrocardiographic abnormalities among black stroke patients to be 76.6% with the associated presence of left axis deviation (52.17% vs 15.22%, p<0.001), left atrial enlargement (17.39% vs 5.80%, p=0.005) and ST segment depression (43.50% vs 21.74%, p=0.001). On the contrary, stroke patients of the Caucasian race were linked to sinus tachycardia (30.44 % vs 13.04%, p=0.002), prolonged QT (49.28% vs 8.70%, p <0.001) and premature ventricular complex (13.04% vs 4.35%, p =0.049) with a concomitant absence of bi-atrial enlargement, low limb lead voltage and non-specific intraventricular block. They had a prevalence of 92%. Unique Contribution to Theory, Policy and Practice: The prevalence of electrocardiographic abnormalities is lower among the black stroke individuals compared to the Caucasians even though the former tend to present with features of structural abnormalities compared to the latter who had more electrical abnormalities. Therefore, in resource-poor settings where ECG cannot readily be carried out, the race of the patient may guide the clinician in suspecting the probable cardiac changes in stroke patients.